Analysis of employee satisfaction, members of a cooperative in Santa Maria - RS (Research, Society and Development, 2022)
The satisfaction of members is a central issue in a cooperative, as they are the ones who carry out development actions. Thus, this work aimed to analyze the satisfaction of the cooperative members of Cooperativa X de Santa Maria. For this, a descriptive and exploratory research was carried out, considered a case study of a quantitative nature. Satisfaction was analyzed using the Job Satisfaction Scale, developed by Siqueira (2008) where five categories were evaluated. Regarding satisfaction with colleagues and satisfaction with leadership, the cooperative members were satisfied, however, around 15% of the cooperative members are dissatisfied with this requirement. With regard to satisfaction with the salary, the highest rates of dissatisfaction occurred, in some of the questions dissatisfaction was paramount, regarding satisfaction with the nature of the work and satisfaction with promotions, the highest rates were those of satisfaction, but the study showed a strong indifference, which indicates a certain detachment with the future of the organization. It is concluded that salary reassessments are necessary, to encourage cooperativism and cooperative education, above all the cooperative must listen more to its member, being able to be an active voice representing its member if necessary.